Pemanfaatan Media Gambar Untuk Meningkatkan Kemampuan Menulis Puisi Siswa Kelas IV SDN Asmorobangun 4 Kediri - Mayske Rinny Liando; Grace Engelin Kuron; Nihriir Ayu Rizky Liliyani (JUPE : Jurnal Pendidikan Mandala, 2022)
Poetry writing skills are one of the obstacles that often occur, because poetry writing skills require high-level thinking skills. A person is said to be unable to write because he does not know what he is writing for, feels he is not talented in writing, does not know how to start a writing and make a work in written form. The use of image media to write poetry is one of the alternative media in learning Indonesian in elementary schools. Media is used to bring up ideas or ideas as the contents of a poem based on ideas from image media. The type of research used in this research is classroom action research (CAR). The purpose of classroom action research is to improve the implementation of the learning process in education, especially in classroom learning and student learning outcomes. This research was conducted at SDN Asmorobangun 4 Kediri with research subjects taken from fourth grade students at SDN Asmorobangun 4 Kediri while the object of research was taken from learning outcomes, especially in the learning process about poetry writing skills for fourth grade students at SDN Asmorobangun 4 Kediri. Based on the results of the research and discussion that have been described, this research can be concluded that there has been an increase in poetry writing skills using image media where in the first cycle of learning one percentage value of students' writing skills is 45% in the less category, while there is an increase in the first cycle of learning II the value of students' writing skills is 65% with a sufficient category, and an increase in the second cycle of learning III where the results of poetry writing skills with a percentage value of 80% with a good category. Based on these learning outcomes, it can be said that the use of image media can improve poetry writing skills in fourth grade students of SDN Asmorobangun 4 Kediri.